Symptomatic Meckel's diverticulum in children: a 12-year survey - Sara Fonseca; Francisco Mourão; Maria Teresa Faria; Sara Fernandes; Ana Catarina Fragoso; José Estevão-Costa (Hygeia Press di Corridori Marinella, 2021)
Introduction: Meckel's diverticulum (MD) is usually asymptomatic but may be associated with severe complications that require awareness. This study aimed to assess the clinical and pathological features of symptomatic MD in children as well as the accuracy of [99mTc]sodium pertechnetate scintigraphy. Methods: We retrospectively reviewed all symptomatic MD in pediatric patients treated between 2007 and 2018 at a tertiary center. Records included demographics, clinical presentation, scintigraphy with [99mTc]sodium pertechnetate, surgical outcome, and histopathology. Results: There were 47 patients (93.6% males) with a median age of 4.31 [1.76-8.10] years. The most common clinical presentation was digestive bleeding (n = 25, 53.2%), followed by intestinal obstruction (n = 12, 25.5%) and diverticulitis (n = 10, 21.3%). The patients with digestive bleeding were younger than those with intestinal obstruction or diverticulitis (2.76 vs. 6.02 years). All patients with digestive bleeding underwent scintigraphy that revealed ectopic gastric mucosa in 23. From the 23 positive scintigraphy, there were 22 available histological exams, from which 21 revealed ectopic gastric mucosa; the 2 negative scintigraphy studies also revealed ectopic gastric mucosa. Therefore, scintigraphy revealed a sensitivity of 91.3% (21/23) in patients presenting digestive bleeding. In the conclusive histological exams (n = 41), ectopic mucosa was detected in 82.9% of cases: 96% in digestive bleeding, 71% in intestinal obstruction, and 60% in diverticulitis. With a median follow-up of 7.2 years, there were no mortality or major complications. Conclusion: Symptomatic MD predominated in males, the digestive bleeding occurring at younger ages. Scintigraphy demonstrated high sensitivity in the detection of ectopic gastric mucosa in patients with digestive bleeding. Overall symptomatic MD usually has ectopic mucosa. Although the surgical outcome is excellent, complications of MD should be kept in mind.